The phenomenology of creative flow: a philosophical reflection from drawing practices (in conversation with Diane Victor) - Woermann, Minka Louisa (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2025.